A compound and an organic light-emitting device
By designing deuterated modified and alkyl-substituted compounds in organic electroluminescent devices, the problem of insufficient device life and efficiency is solved, stability and luminous efficiency are improved, and the performance of hole transport layer is optimized, suitable for electrons Display and OLED lighting equipment.
Patent Information
- Application Number
- CN202411076521.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-07
AI Technical Summary
There are shortcomings in the life and efficiency of existing organic electroluminescent devices, especially as the display area increases, efficiency and life are difficult to improve simultaneously, and the luminescence problem of hole transport layer requires different auxiliary layers, resulting in complex development.
By designing a new compound that combines deuterated modification and alkyl substitution in the molecular structure, optimizes the energy level structure and carrier injection of materials, improves chemical stability and thermal stability, and introduces deuterium at specific locations Instead, it improves the luminous efficiency and the triplet energy level of the material to avoid reverse energy transmission.
It achieves a significant improvement in the stability and life of organic electroluminescent devices, while improving luminous efficiency and voltage, reducing client crosstalk problems, enhancing the lateral resistance of the material, and is suitable for electronic displays and OLED lighting equipment.
Smart Images

Figure CN118580153B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic electroluminescence, and in particular to a compound and an organic light-emitting device. Background Art
[0002] OLED is a current-type organic light-emitting device. It emits light through the injection and recombination of carriers. The luminous intensity is proportional to the injected current. Under the action of the electric field, the holes generated by the anode and the electrons generated by the cathode will move, inject into the hole transport layer and the electron transport layer respectively, and migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, which excite the light-emitting molecules and finally produce visible light.
[0003] In organic light-emitting devices, the biggest issues are lifespan and efficiency, and as the display area becomes larger and larger, such efficiency or lifespan issues must be resolved. Efficiency, lifespan, and driving voltage are interrelated, and when efficiency is improved, the driving voltage is relatively reduced, showing a trend of increasing lifespan. However, efficiency cannot be maximized by simply improving the organic material layer. This is because long lifespan and high efficiency can be achieved simultaneously when the energy level and T1 value between each organic layer are optimally combined with the inherent properties of the material (mobility, interface properties, etc.).
[0004] In addition, in order to solve the luminescence problem of the hole transport layer in recent organic electroluminescent devices, a luminescence auxiliary layer must exist between the hole transport layer and the luminescent layer. Different luminescence auxiliary layers need to be developed according to each luminescent layer (R, G, B). Summary of the invention
[0005] The purpose of the present invention is to provide a compound and an organic electroluminescent device in view of the above technical problems.
[0006] The purpose of the present invention can be achieved by the following measures:
[0007] A compound with a structure as shown in Formula 1:
[0008]
[0009] Ar1 is independently selected from the following substituted or unsubstituted groups: phenyl, biphenyl, naphthyl, anthracenyl, dibenzofuranyl, dibenzothiophenyl, fluorenyl, phenanthrenyl, triphenylfuranyl, wherein the substituent is selected from one or more of deuterium, fluorine, cyano, methyl, deuterated methyl, ethyl, deuterated ethyl, C6-C12 aryl, C6-C12 deuterated aryl, C3-C20 heteroaryl;
[0010] R1 and R2 are independently selected from the following groups, deuterated or undeuterated: C1-C6 alkyl, C5-C8 cycloalkyl, deuterated C6-C20 aryl, and R2 contains at least one deuterium;
[0011] X1-X3 are each independently hydrogen or deuterium.
[0012] Preferably, Ar1 is independently selected from the following substituted or unsubstituted groups: phenyl, biphenyl, dibenzofuranyl, dibenzothienyl, fluorenyl, and the substituent is selected from one or more of deuterium, fluorine, cyano, methyl, deuterated methyl, C6-C12 aryl, C6-C12 deuterated aryl;
[0013] R1 and R2 are independently selected from the following groups, which may be deuterated or not: C1-C6 alkyl, C5-C8 cycloalkyl, deuterated C6-C20 aryl, and R2 contains at least one deuterium.
[0014] Further preferably, Ar1 is selected from the following substituted or unsubstituted groups: phenyl, biphenyl, naphthyl, dibenzofuranyl, dibenzothienyl, fluorenyl, and the substituent is selected from one or more of deuterium, methyl, deuterated methyl, and phenyl;
[0015] R1 and R2 are independently selected from deuterated phenyl, deuterated or undeuterated groups: methyl, ethyl, isopropyl, tert-butyl, cyclopentyl, cyclohexyl, and R2 contains at least one deuterium;
[0016] X1-X3 are all deuterium or all hydrogen.
[0017] More preferably, Ar1 is selected from the following groups:
[0018] The asterisk indicates the connection site;
[0019] R1 is independently selected from deuterated methyl or deuterated phenyl;
[0020] R2 is a deuterated methyl group;
[0021] X1-X3 are all deuterium or all hydrogen.
[0022] In a preferred embodiment, the compound of the present invention can be any one of the following compounds:
[0023] .
[0024] An organic electroluminescent device comprises a first electrode, a second electrode and an organic layer formed between the first electrode and the second electrode, wherein the organic layer contains the organic electroluminescent compound mentioned above.
[0025] Furthermore, the organic layer comprises a hole injection layer, a first hole transport layer, a second hole transport layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer; at least one of the hole injection layer, the first hole transport layer, the second hole transport layer, the light-emitting layer, the hole blocking layer, the electron transport layer, and the electron injection layer contains the above-mentioned organic electroluminescent compound.
[0026] Furthermore, the second hole transport layer contains the above-mentioned organic electroluminescent compound.
[0027] Furthermore, the first hole transport layer contains the above-mentioned organic electroluminescent compound.
[0028] The compound of the invention is applied to the organic electroluminescent device, and the organic electroluminescent device can be used in the field of manufacturing electronic display equipment or OLED lighting equipment.
[0029] Beneficial effects of the present invention:
[0030] The present invention relates to a novel organic electroluminescent material, which achieves synergistic improvement of multiple excellent properties by ingeniously combining deuterated modification and alkyl substitution through careful design of the molecular structure.
[0031] First, the introduction of deuterium improves the chemical and thermal stability of this type of material, thereby greatly improving the stability and life of the device. Deuterium substitution at special positions improves performance while being economical.
[0032] Second, deuteration of the R1 group on the fluorene unit can increase the triplet energy level of the material, avoid reverse energy transfer, and thus improve the luminescence efficiency of the device.
[0033] Third, deuterium alkyl substitution can optimize the energy level structure of the material and promote carrier injection and transport, thereby effectively improving the luminescence efficiency and voltage of the device.
[0034] Fourth, the special linking method of the compound of the present invention improves the hole mobility while strengthening the anisotropy of the material, increasing the lateral resistance of the material and effectively avoiding the problem of client crosstalk. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A schematic diagram of the structure of an organic electroluminescent device provided by the present invention;
[0036] The numbers in the figure represent: 1-anode, 2-hole injection layer, 3-first hole transport layer, 4-second hole transport layer, 5-light-emitting layer, 6-hole blocking layer, 7-electron transport layer, 8-electron injection layer, 9-cathode.
[0037] Figure 2 It is the HPLC chart of compound 9 of the present invention.
[0038] Figure 3 is the DSC spectrum of compound 9 prepared in Example 20 of the present invention, Figure 3 It can be seen that the glass transition temperature Tg value of compound 9 is 126.34°C.
[0039] Figure 4 is the TGA spectrum of compound 9 of the present invention, Figure 4 It can be seen that the thermal gravimetric loss temperature Td value of compound 9 is 384.28°C. DETAILED DESCRIPTION
[0040] The following further illustrates and describes embodiments of various aspects. It should be understood that the description herein is not intended to limit the claims to the specific aspects described. On the contrary, it is intended to cover substitutions, modifications and equivalents that may be included in the spirit and scope of the present disclosure defined by the appended claims.
[0041] As used herein, in "deuterated" or "undeuterated", the term "deuterated" means that at least one hydrogen in the group is re-coordinated with deuterium. The term "undeuterated" means that all hydrogens in the group are not re-coordinated with deuterium.
[0042] The "aromatic group", "aryl" or "aromatic group" herein refers to a group containing one or more aromatic rings, and the aromatic rings here include but are not limited to benzene, naphthalene, phenanthrene, fluorene, acenaphthene, pyridine, pyrimidine, pyrrole, furan, thiophene, etc. The C5-C40 in the C5-C40 aromatic group means that the group contains 5-40 carbon atoms. Aromatic groups can be divided into monocyclic aromatic groups and polycyclic aromatic groups. Specific aromatic groups in the present invention include but are not limited to phenyl, biphenyl, terphenyl, anthracenyl, naphthyl, phenanthryl, fluorenyl, dibenzofuranyl, dibenzothiophenyl, 9,9-spirobifluorenyl, 9,9-dimethylfluorenyl or 9,9-diphenylfluorenyl, etc. Aromatic groups can be substituted and unsubstituted.
[0043] "Cycloalkyl" herein refers to a monocyclic or fused ring ("fused" ring means that each ring in the system shares a pair of adjacent carbon atoms with other rings in the system) group that is all carbon, wherein one or more rings are saturated alicyclic rings, which generally have 3-20 carbon atoms, preferably 3-12 carbon atoms, and more preferably 3-10 carbon atoms. Cycloalkyl can be divided into monocyclic alkyls having only one ring and fused cyclic alkyls having multiple rings. Examples of monocyclic alkyls include, but are not limited to, cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane. Cycloalkyl can be substituted and unsubstituted.
[0044] "Cycloalkenyl" herein refers to a monocyclic or fused ring ("fused" ring means that each ring in the system shares a pair of adjacent carbon atoms with other rings in the system) group that is all carbon, wherein one or more rings do not have a completely connected π electron system and contain at least one alkenyl group, which generally has 3-20 carbon atoms, preferably 3-12 carbon atoms, more preferably 3-10 carbon atoms, and the examples of cycloalkenyl groups include but are not limited to cyclopentene, cyclohexene, cyclohexadiene, cycloheptatriene. Cycloalkenyl groups may be substituted and unsubstituted.
[0045] The "deuterated aromatic group" herein refers to a group in which one or more hydrogen atoms in an aromatic group are substituted with deuterium.
[0046] The "deuterated phenyl group" herein refers to a group in which one or more hydrogen atoms in a phenyl group are replaced by deuterium.
[0047] The “heteroaryl group” herein refers to a heteroaryl group obtained by replacing one or more C atoms in the structure of the “aryl group” with one or more heteroatoms (such as N, O or S).
[0048] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0049] Example 1
[0050] Compound 13 was prepared as follows:
[0051] Step 1:
[0052]
[0053] 1-a (90 g, 0.438 mol, 1 eq) and ultra-dry THF (500 ml) were added to a 2L three-necked flask, cooled to below -65°C, n-butyl lithium (287 ml, 0.46 mol, 1.05 eq) was added dropwise, stirred for 1 h, 1-b (75 g, 0.42 mol, 0.95 eq) in THF (500 ml) was added dropwise, the temperature was slowly raised to room temperature and stirred overnight. The reaction was stopped, quenched with saturated ammonium chloride aqueous solution, stirred and separated, the aqueous phase was extracted with DCM, the organic phases were combined, dried over anhydrous sodium sulfate, and the filtrate was concentrated to dryness under reduced pressure to obtain intermediate 1-c, which was directly used in the next step without purification.
[0054] Add intermediate 1-c (theoretical 129g, 0.42mol, 1eq), triethylsilane (73.3g, 0.63mol, 1.5eq) and DCM (1000ml) to a 2L single-necked flask, cool to below 0°C, add trifluoroacetic acid (143.6g, 1.26mol, 3eq) dropwise, stir and react overnight, and monitor by TLC that intermediate 1-c has basically disappeared. Stop the reaction, add water and stir to extract, wash the organic phase with water once, concentrate the organic phase under reduced pressure, add 500ml petroleum ether and stir to crystallize for 2h, filter by suction, and dry the filter cake at 85°C to obtain 80.1g of light yellow solid 1-d, with a two-step yield of 66.4%.
[0055] 60% sodium hydride (16.6 g, 0.411 mol, 3 eq) and ultra-dry THF (400 ml) were added to a 1L three-necked flask, cooled to below 0°C, and 1-d (39.8 g, 0.137 mol, 1 eq) was added in batches. After the addition was completed, the temperature was raised to 40°C and stirred for reaction for 1 h, then the temperature was lowered to below 0°C, and deuterated iodomethane (24.15 g, 0.21 mol, 1.5 eq) was added dropwise. After the addition was completed, the reaction was stirred at room temperature overnight, and 1-d was monitored by HPLC to be ≤0.1%. The reaction was stopped, water was slowly added to quench, and the liquid was separated by stirring. The aqueous phase was extracted with DCM twice, the organic phases were combined, dried over anhydrous sodium sulfate, and concentrated to dryness under reduced pressure to obtain the intermediate 1-e, which was directly used in the next step without purification.
[0056] Step 2:
[0057] Add intermediate 1-e (42.2 g, 0.137 mol, 1 eq), sodium tert-butoxide (13.2 g, 0.137 mol, 1 eq), deuterated dimethyl sulfoxide (115.1 g, 1.37 mol, 10 eq) and THF (200 ml) to a 2 L three-necked flask, heat to 80 ° C, and stir to react for 48 h. Stop the reaction, cool to room temperature, stir and separate with 1 L water and 200 ml DCM, extract the aqueous phase with DCM twice, combine the organic phases, wash twice with water, dry over anhydrous sodium sulfate, and concentrate to dryness under reduced pressure to obtain intermediate 1-f, which is directly used in the next step without purification.
[0058] In a 2L single-necked flask, intermediate 1-f (42.6 g, 0.137 mol, 1 eq), silver carbonate (7.56 g, 27.4 mmol, 0.2 eq), potassium carbonate (18.9 g, 0.137 mol, 1 eq), diphenylcyclohexylphosphine (18.4 g, 68.5 mmol, 0.5 eq), heavy water (104 g) and toluene (25 ml) were added, the temperature was raised to T = 95 ° C and refluxed, the reaction was carried out for 48 h, the temperature was lowered, 200 ml of dichloromethane was added and stirred, the liquids were separated, the aqueous phase was extracted once with 100 ml of DCM, the organic phases were combined and concentrated, and column chromatography was performed to obtain 26.8 g of off-white solid 1-g, and the three-step yield was 62.3%.
[0059] Step 3:
[0060] 1-g (31.3 g, 0.1 mol, 1 eq), 1-h (36.2 g, 0.1 mol, 1 eq), sodium tert-butoxide (11.5 g, 0.12 mol, 1.2 eq), tri-tert-butylphosphine (8.1 ml, 4 mmol, 0.04 eq) and toluene (400 ml) were added to a 1 L three-necked flask. Tridibenzylideneacetone palladium (1.83 g, 2 mmol, 0.02 eq) was added under N2 protection. After the addition was complete, the temperature was raised to 100 °C and the reaction was stirred. HPLC monitored 1-g ≤ 1%. Stop the reaction, filter through silica gel while hot, concentrate the filtrate to dryness under reduced pressure, add 100 ml of toluene and heat to dissolve, then add 200 ml of ethanol, cool to room temperature for crystallization, filter, recrystallize the filter cake with toluene (150 ml*5) 5 times, dry the filter cake at 85°C to obtain 36.6 g of off-white solid with HPLC purity of 99.9201% and a yield of 52.3%.
[0061] Compounds 15, 18, 26, 31, 73, 109, 115, 133, 140, 145, 157, 161, 164, 177, and 191 were obtained in a similar manner. See Table 1-1, Table 1-2, Table 1-3, Table 1-4, and Table 1-5 for details:
[0062] Table 1-1
[0063]
[0064] Table 1-2
[0065]
[0066] Table 1-3
[0067]
[0068] Table 1-4
[0069]
[0070] Table 1-5
[0071]
[0072] Embodiment 17
[0073]
[0074] Compound 22 was prepared as follows
[0075] Step 1:
[0076]
[0077] Compound 17-a (101.74 g, 0.628 mol, 1 eq) and ultra-dry THF (500 ml) were added to a 2L three-necked flask, cooled to below -65°C, n-butyl lithium (412 ml, 0.66 mol, 1.05 eq) was added dropwise, stirred at room temperature for 1 h, and a solution of 17-b (123.0 g, 0.6 mol, 0.95 eq) in ultra-dry THF (100 ml) was added dropwise, and stirred at room temperature overnight to react. The reaction was stopped, 800 ml of saturated ammonium chloride aqueous solution was added to quench, stirred and separated, the aqueous phase was extracted with DCM, the organic phases were combined, dried over anhydrous sodium sulfate, and the filtrate was concentrated to dryness under reduced pressure to obtain intermediate 17-c, which was directly used in the next step without purification.
[0078] 17-c (172.9 g, 0.6 mol, 1 eq), I2 (242 g, 0.96 mol, 1.6 eq), potassium carbonate (248 g, 1.8 mol, 3 eq) and tert-butyl alcohol (600 ml) were added to a 2 L three-necked flask. Under N2 protection, the temperature was raised to 90 °C and stirred for reaction for 20 h to 24 h. The reaction was stopped, quenched by adding 800 ml of 50% sodium thiosulfate aqueous solution, extracted 3 times by adding EA (300 ml*3), the organic phases were combined, washed 2 times with water, dried over anhydrous sodium sulfate, filtered, and the filtrate was concentrated to dryness under reduced pressure to obtain 157.99 g of yellow oil 17-d, with a two-step yield of 98.2%. The above operation was repeated.
[0079] Step 2:
[0080]
[0081] 17-d (178.69 g, 0.62 mol, 1 eq) and ultra-dry THF (500 ml) were added to a 2L three-necked flask, cooled to below -65°C, n-butyl lithium (407 ml, 0.651 mol, 1.05 eq) was added dropwise, stirred at room temperature for 30 min, and a solution of 17-e (165 g, 0.589 mol, 0.95 eq) in ultra-dry THF (100 ml) was added dropwise, and stirred at room temperature overnight. The reaction was stopped, quenched by adding 800 ml of saturated ammonium chloride aqueous solution, stirred and separated, the aqueous phase was extracted with DCM, the organic phases were combined, dried over anhydrous sodium sulfate, and the filtrate was concentrated to dryness under reduced pressure to obtain 17-f, which was repeated without purification and directly used in the next step.
[0082] 17-f (259.4 g, 0.589 mol, 1 eq) and DCM (800 ml) were added to a 2L single-necked flask, cooled to below 0°C, and methanesulfonic acid (226 g, 2.356 mol, 4 eq) was added. After the addition was completed, the mixture was stirred at room temperature for 1-2 hours. HPLC was used to monitor 17-f ≤ 5%. The reaction was stopped, 200 ml of ethanol was added, and most of the DCM was removed by vacuum concentration at low temperature until there was almost no droplets. The filter cake was filtered, and the filter cake was rinsed with ethanol for 3-4 times. The filter cake was dried at 85°C by air blast to obtain 174.4 g of gray solid 17-g, with a two-step yield of 70.1%.
[0083] Step 3:
[0084]
[0085] 17-g (42.2 g, 0.1 mol, 1 eq), 17-h (36.2 g, 0.1 mol, 1 eq), sodium tert-butoxide (11.5 g, 0.12 mol, 1.2 eq), tri-tert-butylphosphine (8.1 ml, 4 mmol, 0.04 eq) and toluene (400 ml) were added to a 1 L three-necked flask. Tridibenzylideneacetone palladium (1.83 g, 2 mmol, 0.02 eq) was added under N2 protection. After the addition was complete, the temperature was raised to 100 °C and the reaction was stirred. HPLC monitored 17-g ≤ 1%. Stop the reaction, filter through silica gel while hot, concentrate the filtrate to dryness under reduced pressure, add 100 ml of toluene and heat to dissolve, then add 200 ml of ethanol, cool to room temperature for crystallization, filter, recrystallize the filter cake with toluene (150 ml*5) 5 times, and dry the filter cake at 85°C to obtain 32.2 g of off-white solid 22 with HPLC purity of 99.9322% and a yield of 45.8%.
[0086] Compounds 1, 7, 9, 11, 19, 24, 51, 61, 70, 72, 77, 80, 105, 125, 142, 148, 149, 151, 172, 173, 181, 188 were obtained in a similar manner. See Table 2-1, Table 2-2, Table 2-3, Table 2-4, Table 2-5, Table 2-6, Table 2-7 for details:
[0087] Table 2-1
[0088]
[0089] Table 2-2
[0090]
[0091] Table 2-3
[0092]
[0093] Table 2-4
[0094]
[0095] Table 2-5
[0096]
[0097] Table 2-6
[0098]
[0099] Table 2-7
[0100]
[0101] The synthesis and identification results of the compounds prepared in Table 1-1, Table 1-2, Table 1-3, Table 1-4, Table 1-5, Table 2-1, Table 2-2, Table 2-3, Table 2-4, Table 2-5, Table 2-6, and Table 2-7 above are shown in Table 3 below:
[0102] Table 3
[0103] Compound FD-Quality Compound FD-Quality 1 m / z=699.91(C53H32D9N=700.38) 109 m / z=651.95(C48H28D9NO=652.34) 7 m / z=715.86(C54H32D11N=716.41) 115 m / z=667.87(C48H28D9NS=668.32) 9 m / z=701.95(C53H30D11N=702.39) 125 m / z=699.17(C53H33D8N=699.37) 11 m / z=727.87(C55H36D9N=728.41) 133 m / z=667.94(C48H28D9NS=668.32) 13 m / z=637.79(C48H30D9N=638.36) 140 m / z=635.21(C48H33D6N=635.35) 15 m / z=663.84(C50H36D7N=664.38) 142 m / z=699.93(C53H32D9N=700.38) 18 m / z=655.11(C49H29D12N=655.40) 145 m / z=691.24(C52H41D6N=691.41) 19 m / z=715.86(C54H32D11N=716.41) 148 m / z=699.77(C53H32D9N=700.38) 22 m / z=701.93(C53H30D11N=702.39) 149 m / z=713.89(C54H34D9N=714.40) 24 m / z=727.83(C55H36D9N=728.41) 151 m / z=715.85(C54H32D11N=716.41) 26 m / z=637.85(C48H30D9N=638.36) 157 m / z=651.94(C49H32D9N=652.38) 31 m / z=651.88(C49H32D9N=652.38) 161 m / z=649.10(C58H43D6N=649.36) 51 m / z=701.80(C53H30D11N=702.39) 164 m / z=665.18(C48H31D6NS=665.30) 61 m / z=791.92 (C59H32D11NO=792.40) 172 m / z=789.24 (C59H35D8NO=789.38) 70 m / z=729.10(C54H31D10NO=729.38) 173 m / z=717.19(C54H31D12N=717.41) 72 m / z=791.93(C59H32D11NO=792.40) 177 m / z=725.17(C54H35D6NO=725.36) 73 m / z=727.87 (C54H32D9NO=728.38) 181 m / z=713.83(C53H30D9NO=714.36) 77 m / z=719.23(C54H29D14N=719.43) 188 m / z=713.24(C53H31D8NO=713.35) 80 m / z=757.98(C56H34D11NO=758.42) 191 m / z=649.12(C48H31D6NO=649.33) 105 m / z=715.88(C53H28D11NO=716.37)
[0104] The above materials were subjected to basic performance tests, including thermal weight loss temperature Td and glass transition temperature Tg. The test results are shown in Table 4 below.
[0105] Note: Thermal weight loss temperature Td is the temperature at which the weight loss ratio is 5% in a nitrogen atmosphere, and is measured on a TGA N-1000 thermogravimetric analyzer with a nitrogen flow rate of 10 mL / min. Tg (glass transition temperature) is measured by differential scanning calorimetry (DSC, Shinco DSC N-650) with a heating rate of 10°C / min.
[0106] Table 4
[0107] Test material (compound) Tg / ℃ Td / ℃ Test material (compound) Tg / ℃ Td / ℃ 1 112.35 390.18 109 109.78 367.45 7 115.24 394.27 115 119.62 378.57 9 126.34 384.28 125 120.54 392.18 11 131.71 416.21 133 111.42 387.65 13 110.35 391.25 140 104.17 370.71 15 121.47 401.24 142 119.48 386.48 18 127.69 408.22 145 118.11 394.53 19 129.71 411.68 148 115.80 382.41 22 126.84 398.87 149 123.54 400.13 24 121.46 388.35 151 129.40 413.42 26 107.33 362.64 157 103.24 380.26 31 110.50 381.32 161 114.48 378.17 51 111.71 382.06 164 118.10 387.91 61 129.83 391.53 172 138.57 379.48 70 121.26 380.77 173 127.66 378.69 72 125.71 394.52 177 123.48 381.63 73 118.68 379.34 181 120.31 375.70 77 114.17 375.78 188 125.64 367.99 80 120.61 385.54 191 104.34 372.43 105 107.46 371.24
[0108] According to the above data, the compounds synthesized in the present invention have excellent thermal stability, which means that the compounds conforming to the general structural formula of the present invention have excellent thermal stability and can meet the requirements for the use of organic electroluminescent materials.
[0109] Device performance test:
[0110] Application Example 1:
[0111] ITO was used as the reflective layer anode substrate material, and its surface was treated with water, acetone, and N2 plasma in sequence;
[0112] On top of the ITO anode substrate, 10 nm of HT-1 doped with 2% by mass of NDP-9 was deposited to form a hole injection layer (HIL);
[0113] 100 nm of HT-1 was evaporated on the hole injection layer (HIL) to form the first hole transport layer (HTL);
[0114] Vacuum evaporation of the compound 9 designed by the present invention on the first hole transport layer (HTL) to form a second hole transport layer (GPL) with a thickness of 30 nm;
[0115] Compounds G1 and G2 were co-evaporated at a mass ratio of 5:5 as green light host materials, and GD-1 was evaporated as a doping material (the amount of GD-1 was 8% of the total mass of G1 and G2) on the second hole transport layer (GPL) to form a light-emitting layer with a thickness of 30 nm;
[0116] HB-1 was evaporated onto the light-emitting layer to obtain a hole blocking layer (HBL) with a thickness of 20 nm;
[0117] ET-1 and LiQ were co-evaporated onto the hole blocking layer (HBL) in a mass ratio of 5:5 to obtain an electron transport layer (ETL) with a thickness of 30 nm;
[0118] Magnesium (Mg) and silver (Ag) were mixed and evaporated on the electron transport layer (ETL) in a mass ratio of 9:1 to form an electron injection layer (EIL) with a thickness of 50 nm;
[0119] Thereafter, silver (Ag) is evaporated onto the electron injection layer to form a cathode with a thickness of 100 nm, and a DNTPD with a thickness of 50 nm is deposited on the cathode sealing layer. In addition, the cathode surface is sealed with a UV curable adhesive and a sealing film (seal cap) containing a dehumidifier to protect the organic electroluminescent device from being affected by oxygen or moisture in the atmosphere. Thus, an organic electroluminescent device is prepared.
[0120]
[0121]
[0122] .
[0123] Application Example 2-39
[0124] Compounds 1, 7, 11, 13, 15, 18, 19, 22, 24, 26, 31, 51, 61, 70, 72, 73, 77, 80, 105, 109, 115, 125, 133, 140, 142, 145, 148, 149, 151, 157, 161, 164, 172, 173, 177, 181, 188, and 191 in Examples 2-39 of the present invention are respectively used as the second hole transport material, and the other parts are consistent with those in Application Example 1, and organic electroluminescent devices of Application Examples 2-39 are prepared accordingly.
[0125] Comparative Examples 1-8:
[0126] The difference from Application Example 1 is that compounds D1, D2, D3, D4, D5, D6, D7 and D8 are used as the second hole transport material respectively, and the rest is the same as Application Example 1.
[0127] The characteristics of the organic electroluminescent device manufactured in the above application example and the organic electroluminescent device manufactured in the control example were measured under the condition of a current density of 10 mA / cm2. The results are shown in Table 5 below.
[0128] Table 5
[0129] Experimental Group Second hole transport layer <![CDATA[Current density (mA / cm 2 )]]> Voltage (V) Luminous efficiency Emitting color Comparative Example 1 D1 10 3.70 131.3 Green Light Comparative Example 2 D2 10 3.72 144.2 Green Light Comparative Example 3 D3 10 3.80 158.1 Green Light Comparative Example 4 D4 10 3.67 152.3 Green Light Comparative Example 5 D5 10 3.70 141.5 Green Light Comparative Example 6 D6 10 3.62 150.2 Green Light Comparative Example 7 D7 10 3.81 157.4 Green Light Comparative Example 8 D8 10 3.64 142.5 Green Light Application Example 1 9 10 3.22 196.6 Green Light Application Example 2 1 10 3.30 174.3 Green Light Application Example 3 7 10 3.34 185.2 Green Light Application Example 4 13 10 3.25 188.7 Green Light Application Example 5 11 10 3.35 179.4 Green Light Application Example 6 15 10 3.44 171.2 Green Light Application Example 7 18 10 3.30 173.5 Green Light Application Example 8 19 10 3.27 181.6 Green Light Application Example 9 22 10 3.28 189.8 Green Light Application Example 10 24 10 3.34 184.5 Green Light Application Example 11 26 10 3.32 175.9 Green Light Application Example 12 31 10 3.30 171.4 Green Light Application Example 13 51 10 3.28 181.4 Green Light Application Example 14 61 10 3.24 179.4 Green Light Application Example 15 70 10 3.29 174.2 Green Light Application Example 16 72 10 3.28 171.5 Green Light Application Example 17 73 10 3.40 176.8 Green Light Application Example 18 77 10 3.29 185.6 Green Light Application Example 19 80 10 3.27 179.5 Green Light Application Example 20 105 10 3.22 177.1 Green Light Application Example 21 109 10 3.34 181.1 Green Light Application Example 22 115 10 3.38 182.4 Green Light Application Example 23 125 10 3.28 178.7 Green Light Application Example 24 133 10 3.25 181.6 Green Light Application Example 25 140 10 3.40 169.3 Green Light Application Example 26 142 10 3.33 182.7 Green Light Application Example 27 145 10 3.41 170.5 Green Light Application Example 28 148 10 3.34 181.6 Green Light Application Example 29 149 10 3.27 176.2 Green Light Application Example 30 151 10 3.24 179.5 Green Light Application Example 31 157 10 3.35 166.3 Green Light Application Example 32 161 10 3.42 170.9 Green Light Application Example 33 164 10 3.38 168.4 Green Light Application Example 34 172 10 3.28 178.1 Green Light Application Example 35 173 10 3.34 172.1 Green Light Application Example 36 177 10 3.36 167.9 Green Light Application Example 37 181 10 3.28 181.7 Green Light Application Example 38 188 10 3.24 180.2 Green Light Application Example 39 191 10 3.39 170.8 Green Light
[0130] As can be seen from the above table, when the compounds of the present invention are applied to organic electroluminescent devices, at the same current density, the luminous efficiency is greatly improved, the starting voltage of the device is reduced, and the power consumption of the device is relatively reduced.
[0131] The organic electroluminescent devices prepared in the control examples 1-8, application examples 1-13, and 23-24 were respectively subjected to luminescence life tests to obtain luminescence life T97% data (the time when the luminescence brightness decreases to 97% of the initial brightness). The test equipment was a TEO luminescent device life test system. The results are shown in Table 6:
[0132] Table 6
[0133] Experimental Group Hole Transport Materials (HTL) <![CDATA[Current density (mA / cm 2 )]]> T97% Comparative Example 1 D1 10 100% Comparative Example 2 D2 10 95% Comparative Example 3 D3 10 102% Comparative Example 4 D4 10 105% Comparative Example 5 D5 10 96% Comparative Example 6 D6 10 108% Comparative Example 7 D7 10 90% Comparative Example 8 D8 10 98% Application Example 1 9 10 142% Application Example 2 1 10 131% Application Example 3 7 10 138% Application Example 4 13 10 139% Application Example 5 11 10 124% Application Example 6 15 10 116% Application Example 7 18 10 122% Application Example 8 19 10 131% Application Example 9 22 10 132% Application Example 10 24 10 136% Application Example 11 26 10 123% Application Example 12 31 10 127% Application Example 13 51 10 133% Application Example 23 125 10 147% Application Example 24 133 10 137%
[0134] It can be seen from the above table that when the compound of the present invention is applied to an organic electroluminescent device, the service life is greatly improved at the same current density, and the compound has broad application prospects.
[0135] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A compound, It is characterized in that Selected from the compounds shown in formula 1: ; Ar 1 Selected from the following groups: The asterisk indicates the connection site; R 1 Independently selected from deuterated methyl or deuterated phenyl; R 2 is independently selected from deuterated phenyl, deuterated or undeuterated groups: methyl, ethyl, isopropyl, tert-butyl, cyclopentyl, cyclohexyl, and R 2 Contains at least 1 deuterium; X 1 -X 3 All are deuterium or all are hydrogen.
2. A compound according to claim 1, It is characterized in that The compound is one of the following structural compounds: 。 3. An organic electroluminescent device comprising the compound according to claim 1, It is characterized in that The organic electroluminescent device comprises a first electrode, a second electrode and an organic layer formed between the first electrode and the second electrode, wherein the organic layer contains the organic electroluminescent compound according to any one of claims 1 to 2.
4. The organic electroluminescent device according to claim 3, It is characterized in that The organic layer comprises a hole injection layer, a hole transport layer, a second hole transport layer, a light-emitting layer, a hole blocking layer, an electron transport layer, and an electron injection layer; at least one of the hole injection layer, the hole transport layer, the second hole transport layer, the light-emitting layer, the hole blocking layer, the electron transport layer, and the electron injection layer contains the organic electroluminescent compound described in any one of claims 1 to 2.
5. The organic electroluminescent device according to claim 4, It is characterized in that The second hole transport layer contains the organic electroluminescent compound according to any one of claims 1 to 2.
6. The organic electroluminescent device according to claim 4, It is characterized in that The hole transport layer contains the organic electroluminescent compound according to any one of claims 1 to 2.
7. The organic electroluminescent device according to claim 3, It is characterized in that The compound is applied to the organic electroluminescent device, and the organic electroluminescent device is used in the field of manufacturing electronic display equipment or OLED lighting equipment.
